The Value Chain Circulation of Chinese Multinational Corporations in the Context of the Dual-Circulation—Taking SAIC as an example - Lingtong Zhu, Xin Hua (Forest Chemicals Review, 1970)
This article measures and evaluates the value chain circulation performance of Chinese automotive multinational corporations based on the value chain theory by taking SAIC as an example in the context of the dual-circulation. The study found that Chinese automotive multinationals have low value chain status, poor cycle efficiency, and weak brand influence under the background of the dual-circulation. The main reasons include insufficient R&D investment, lack of an independent and controllable internal circulation industrial chain; unreasonable market structure and weak overseas marketing capabilities of independent brands; imperfect dual-circulation after-sales service system, etc. Based on these, this article puts forward countermeasures such as expanding the scale of R&D investment, realizing the independent control of the internal recycling industry chain; optimizing the market structure, enhancing the overseas marketing capabilities of independent brands; building a complete dual-circulation after-sales service system. It hopes to provide a reference for Chinese automotive multinational companies to realize the improvement of value chain status and the improvement of value chain circulation performance under the background of dual-circulation.